Modelling of micro hydroelectric system design - Ibrahim, Noor Azliza (2012)
Hydropower is emerging as a major contributor to the world energy requirement. It's inexhaustible, clean and has many other benefits as it does not encounter the problems of population displacement and environmental problems. Stand-alone Power System (SPS) or formerly known as Remote Area Power Supply System (RAPS) is the power system not connected to the grid. Today, there are many rural areas still not readily accessible of grid power due to constraints of distance and terrain. Small (SPS) of renewable energy are targeted to the areas since there is not economic and environmental friendly by obtaining electricity from diesel generators. This project is describing model design of stand-alone micro hydropower system. The models simulation is achieved by using MATLAB SIMULINK software.